2007
DOI: 10.1007/s10096-007-0433-y
|View full text |Cite
|
Sign up to set email alerts
|

Strong slime production is a marker of clinical significance in Staphylococcus epidermidis isolated from intravascular catheters

Abstract: Biofilm production was assessed in 52 Staphylococcus epidermidis isolates from the catheters of 52 patients with catheter-related bloodstream infections (CR-BSI) and compared with 14 isolates from the skin of healthy volunteers by spectrophotometry. The isolates were classified as non- (G1), weak- (G2) or strong- (G3) slime producers based on optical density, and as producers and non-producers based on the results of the Congo red agar test. Differences (p = 0.012) in the proportion of G1, G2 and G3 among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 12 publications
0
17
1
Order By: Relevance
“…The results from other workers showed a high percentage of up to 90% of S. epidermidis isolated from infections associated with indwelling medical devices were biofilm producers. In contrast, a relatively lower percentage of biofilm producers were present in the skin, 35.7% and 64.3% were non-biofilm formers and weak biofilm producers, respectively (29). Similarly, only 32% from skin and nasal swabs showed biofilm production while 70% of invasive staphylococcal strains isolated from blood of patients hospitalized with peripheral intravenous devices exhibited biofilm forming ability (22).…”
Section: Detection Of Biofilm Formation By the Congo Red Agar Methodsmentioning
confidence: 92%
“…The results from other workers showed a high percentage of up to 90% of S. epidermidis isolated from infections associated with indwelling medical devices were biofilm producers. In contrast, a relatively lower percentage of biofilm producers were present in the skin, 35.7% and 64.3% were non-biofilm formers and weak biofilm producers, respectively (29). Similarly, only 32% from skin and nasal swabs showed biofilm production while 70% of invasive staphylococcal strains isolated from blood of patients hospitalized with peripheral intravenous devices exhibited biofilm forming ability (22).…”
Section: Detection Of Biofilm Formation By the Congo Red Agar Methodsmentioning
confidence: 92%
“…Moreover, biofilm formation in vitro can be correlated with virulence in vivo (43,66). Native-valve endocarditis caused by viridans group streptococci may not fit the strict definition of a biofilm.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus epidermidis strains from different sources exhibit genetic differences. It is reported that S. epidermidis isolated from infections associated with clinical catheters differ from those isolated from normal human skin [6][7][8][9]. The positive rate of bacterial biofilm-related genes, such as fbe, atlE, and icaADB, varies with different sources as well.…”
mentioning
confidence: 99%
“…The positive rate of icaADB gene was 57.1% (64/112). Staphylococcus epidermidis with different genetic background often showed different biologic characteristics, and whether S. epidermidis can form biofilm is the major criterion to distinguish between symbiotic and invasive S. epidermidis [3,9]. Studies on the biofilm formation of S. epidermidis showed that the enzyme responsible for biofilm formation is encoded by ica operon, which include icaR (regulatory gene), icaA, icaD, icaB, and icaC genes existing in series connection.…”
mentioning
confidence: 99%